Association between serum vitamin D levels and prostate cancer: A cross-sectional analysis (Annals of Medical Research, 2025)
Aim: This study aims to examine whether inflammatory parameters such as vitamin D, CRP, and sedimentation measured in the serum of patients diagnosed with prostate cancer are different from those of their healthy peers.Materials and Methods: The results of 163 patients who applied to Ordu University Urology Clinic with a diagnosis of prostate cancer between December 2019 and December 2023 and 140 healthy men who applied for other reasons in the same period were examined. Vitamin D levels and inflammatory markers such as CRP and ESR were compared between groups.Results: The age distribution of patients in the prostate cancer and control group was 66.9±8.6 and 61.8±7.6 years, respectively. The vitamin D levels were identified as 17.25 [9.18] (5.27 – 55) µg/L and 20.74 [7.98] (6.94 – 51.01) in the prostate cancer and control group, respectively (p=0.001). Additionally, inflammatory markers like CRP and ESR were identified to be high in the prostate cancer group (p
Keywords: Prostate cancer; Vitamin D; Inflammation; Marker